Zosteriform cutaneous metastases from a carcinoma mammae - Widiasri, Kharisma Yuliasis; Sayekti, Ayu Wikan; Febiyanto, Novian; Wahyuanggradewi, Elliana; Giantoro, Jeffrey; Pudjiati, Satiti Retno; Rinonce, Hanggoro Tri; Siswati, Agnes Sri (Journal of General - Procedural Dermatology and Venereology Indonesia, 2023)
Background: Cutaneous metastases were reported in 18.6-26.5% of breast cancer patients. Zosteriform cutaneous metastasis is an unusual and rare morphological variant. Clinicians, especially dermatovenereologists, should consider dermatomal cutaneous metastases in oncology patients aside from herpes zoster, which is common in this population. Case Illustration: A 62-year-old woman presented with clustered papules and vesicles with an erythematous base, sometimes painful, on the right side of the chest in T5-T7 dermatomal distribution of 1-month duration. She had undergone a radical mastectomy for breast carcinoma and had been receiving chemoradiotherapy, which was completed in March 2018. A diagnosis of zosteriform cutaneous metastases was established after discovering malignant cells in the representative lesion via biopsy, similar to those sampled from the previous cancerous right mammary tissue. Discussion: Zosteriform cutaneous metastasis is a rare occurrence, with a variety of clinical backgrounds, morphological, and histological features that can influence the clinical course of the disease. The mechanism for the occurrence of zosteriform cutaneous metastasis remains uncertain; several studies reported possible causes: Koebner-like reactions at the site of previous herpes zoster infections, perineural lymphatic spread, spread through blood vessels associated with the dorsal ganglion, unintentional implantation during surgery, direct invasion of the underlying structure (primary cancer), and spread from the lymphatic system. This case suits the diagnosis of zosteriform cutaneous metastases based on lesion morphology, location, distribution, and histopathological features matching those of the primary tumor. Conclusion: Metastatic disease should be considered in the differential diagnosis of zosteriform rash in oncology patients.